2021
DOI: 10.1016/j.energy.2021.120876
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mask waste to energy via thermochemical pathway: Effect of Co-Feeding food waste

Abstract: In this study, co-pyrolysis of single-use face mask (for the protection against COVID-19) and food waste was investigated for the purpose of energy and resource valorization of the waste materials. To this end, disposable face mask (a piece of personal protective equipment) was pyrolyzed to produce fuel-range chemicals. The pyrolytic gas evolved from the pyrolysis of the single-use face mask consisted primarily of non-condensable permanent hydrocarbons such as CH 4 , C 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…The precursor to the production of activated carbons were disposable face masks manufactured by AP PROPERTY S.A. (Poland). According to the literature the average carbon content of the precursor material – surgical mask was 75.9% [41] , [42] . A saturated KOH solution was used as the chemical activating agent.…”
Section: Methodsmentioning
confidence: 99%
“…The precursor to the production of activated carbons were disposable face masks manufactured by AP PROPERTY S.A. (Poland). According to the literature the average carbon content of the precursor material – surgical mask was 75.9% [41] , [42] . A saturated KOH solution was used as the chemical activating agent.…”
Section: Methodsmentioning
confidence: 99%
“…When pyrolyzing herbal medicine waste with food waste with a ratio of 50:50 at 700 °C, it led to 1.9% H 2 selectivity [ 24 ]. The co-pyrolysis of a 1:1 mixture of face mask and food waste gave 1.6% H 2 selectivity at 700 °C [ 23 ]. At a comparable temperature and feedstock composition, the co-pyrolysis of single-use food containers and corrugated fiberboard exhibited 1.2% H 2 selectivity (this study).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the co-pyrolysis of the single-use food containers and corrugated fiberboard resulted in no phenolic compounds or polycyclic aromatic compounds (0% selectivity), while significant amounts of phenolic compounds and polycyclic aromatic compounds were found (>20% selectivity) in the corrugated fiberboard-derived pyrolytic liquid. Although other co-pyrolysis processes (e.g., wood bark/food waste [ 25 ], herbal medicine waste/food waste [ 24 ], and face mask/food waste [ 23 ]) have been reported to suppress the formation of such compounds, those processes resulted in a pyrolytic product containing certain amounts of phenolic compounds and polycyclic aromatic compounds. This should indicate that the addition of the single-use food containers suppresses the formation of phenolic compounds and polycyclic aromatic compounds during the pyrolysis of the corrugated fiberboard.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 , 9 , 10 ] Just for the year 2020, it was estimated that about 1.56 billion surgical face masks entered into oceanic bodies, which would be nearly equal to 4680–6240 metric tons of waste plastic. [ 11 , 12 ] Such a huge volume of plastics and microplastics entering into the aquatic domains can potentially harm the marine creatures upon the ingestion or getting stuck into the plastic masks, which may either annihilate them in a direct way (i. e., impairment of reproduction and growth of young mammals) and/or render them more vulnerable to the other dangers. [ 13 , 14 , 15 ] In addition to marine life, waste face masks are also becoming the cause of premature deaths of fauna and flora due to choking and suffocating entanglement.…”
Section: Introductionmentioning
confidence: 99%
“… [20] In another study, it was found that during the pyrolysis of disposable face masks non‐condensable hydrocarbons of great importance from a fuel point of view, such as CH 4 , C 2 H 4 , C 2 H 6 , C 3 H 6 and C 3 H 8 , are evolved. [11] Aragaw and Mekonnen launched a research to identify the polymer type of face masks and gloves and analyzed their transformation into crude oil via pyrolysis. [21] Chen et al.…”
Section: Introductionmentioning
confidence: 99%